Creditor protection, judicial enforcement and credit access - Annalisa Ferrando; Daniela Maresch; Andrea Moro (European Central Bank (ECB), 2015)
We investigate the role of the judicial system on whether or not the firms obtain the credit they applied for, by looking at the strength of the creditor protection, the strength of property rights, the time for resolving a dispute, its costs and the number of procedures the plaintiff faces. We use data about 48,590 firms from eleven countries collected via the Survey on the Access to Finance of Enterprises (European Central Bank) and data from the World Bank, the Heritage Foundation and Eurostat. The results suggest that the better the judicial enforcement system is (reduced costs, reduced time, and limited number of procedures) and the higher the creditor protection is (high overall strength of the legal system, high property rights protection), the lower the probability that the firms are credit constrained. Our results are robust to selection bias (Heckman selection) as well as different controls and different estimation techniques. More importantly, we find that these variables have considerable economic impact: the probability to obtain credit is up to 40% higher in countries with a better legal system.
Keywords: G21; G28; K41; 330; Credit Access; Creditor Protection; Judicial System; Property Rights